What do petrochemical workers, healthcare workers, and truck drivers have in common? Evaluation of sleep and alertness in Brazilian shiftworkers O que têm em comum os trabalhadores da indústria petroquímica, profissionais de saúde e caminhoneiros? Sono e vigília entre trabalhadores em turnos no Brasil - Frida Marina Fischer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
The article reports briefly on some effects of shiftwork and the work environment on health and wellbeing of shiftworkers. Studies of Brazilian shiftworkers (healthcare workers, petrochemical workers, and truck drivers) are described. A similar methodology was used to evaluate sleep and alertness in all these studies. The evaluation of sleep duration and quality and alertness showed similar results in the three studies. Although the workers were in different work settings, performing different jobs, the results are similar: daytime sleep is reduced and perceived as having worse quality than nighttime sleep; alertness decreases as the night work progresses. The study highlights the importance of shiftwork schedules' features and work organization for workers' health, wellbeing, and safety. Este artigo apresenta de forma resumida os efeitos do trabalho em turnos na saúde e bem-estar dos trabalhadores. São apresentados estudos conduzidos em hospitais, indústria petroquímica e companhias de caminhões de carga. Foi utilizada metodologia semelhante nos estudos descritos para avaliação da duração e qualidade do sono, assim como do alerta durante o trabalho. Apesar dos trabalhadores realizarem tarefas bastante distintas, os resultados das avaliações de sono e alerta foram semelhantes: os trabalhadores após turnos noturnos apresentaram sono mais curto do que após outros turnos, comparados consigo mesmos e/ou com seus colegas de turnos diurnos. É enfatizada a importância da escala em turnos, assim como da organização do trabalho, para auxiliar os trabalhadores a manterem sua saúde, bem-estar e segurança no trabalho.